2003
DOI: 10.1097/00006676-200305000-00020
|View full text |Cite
|
Sign up to set email alerts
|

An Orthotopic Nude Mouse Model for Evaluating Pathophysiology and Therapy of Pancreatic Cancer

Abstract: Orthotopic implantation of donor tumor fragments into nude mice is technically feasible and is superior to the cell injection technique. It results in reproducible local and systemic development of pancreatic cancer that mimics the human disease. A dissemination score may help to better quantify therapeutic effects in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 19 publications
3
75
0
Order By: Relevance
“…However, it is conceivable that the development of efficacious therapeutic treatments for human cancers relies significantly upon the presence and activity of the primary oncogene target. 46 In our study, the tumoral regression observed with local administration of Ad/ETS-1-DN appears to be significantly higher when the ETS-1 is abundantly expressed (Figure 1). However, IHC revealed that ETS-1 appears to be expressed more strongly in islets than in normal pancreatic ductal tissue or HPDEC-6 cells.…”
supporting
confidence: 53%
“…However, it is conceivable that the development of efficacious therapeutic treatments for human cancers relies significantly upon the presence and activity of the primary oncogene target. 46 In our study, the tumoral regression observed with local administration of Ad/ETS-1-DN appears to be significantly higher when the ETS-1 is abundantly expressed (Figure 1). However, IHC revealed that ETS-1 appears to be expressed more strongly in islets than in normal pancreatic ductal tissue or HPDEC-6 cells.…”
supporting
confidence: 53%
“…Thus, tissue-specific interactions between tumor cells and the surrounding compartments, increasingly recognized as the major determinants of tumor phenotype, are maintained [15,16]. These models preserve the histological architecture between the original tumors and their tumorgrafts and throughout generations, an essential trait that is hardly recapitulated by other approaches such as those based on cells inoculation into the pancreas or by implantation of subcutaneous donor tumors [17][18][19]. Moreover, although fibrosis experimented a substantial decrease with respect to primary tumors, these tumorgrafts maintained a significant desmoplasia degree through generations Interestingly, transition zones between tumor, fibrotic tissue and normal pancreas can be observed (Supplemental 3).…”
Section: Discussionmentioning
confidence: 99%
“…Three-micrometer-thin tissue sections were obtained and stained according to the immunohistochemical method described above. A dissemination score was developed to assess local tumor infiltration as well as distant metastasis (27)…”
Section: Methodsmentioning
confidence: 99%
“…Five human pancreatic cancer cell lines (AsPC-1, Capan-1, HPAF-2, MiaPaCa-2, and Panc-1) were examined for their expression of Snail, Slug, and Twist as well as for E-cadherin and N-cadherin by reverse transcription-PCR (RT-PCR), real-time PCR, and Western blotting. Moreover, we analyzed the local expression of our targets in vivo in an orthotopic nude mouse model of pancreatic cancer (27) by immunohistochemistry.…”
mentioning
confidence: 99%